The HipAB Toxin–Antitoxin System Stabilizes a Composite Genomic Island in Shewanella putrefaciens CN-32 - Zhao, Yi; Wang, Weiquan; Yao, Jianyun; Wang, Xiaoxue; Liu, Dong; Wang, Pengxia (Frontiers in Microbiology, 2022)
Composite genomic islands (GIs) are useful models for studying GI evolution if they can revert into the previous components. In this study, CGI48 – a 48,135-bp native composite GI that carries GI21, whose homologies specifically integrated in the conserved yicC gene – was identified in Shewanella putrefaciens CN-32. CGI48 was integrated into the tRNATrp gene, which is a conserved gene locus for the integration of genomic islands in Shewanella. Upon expressing integrase and excisionase, CGI48 and GI21 are excised from chromosomes via site-specific recombination. The imperfect attachment sites of GI21 facilitated the capture of GI21 into CGI48. Moreover, GI21 encodes a functional HipBA toxin-antitoxin system, thus contributing to the maintenance of CGI48 in the host bacteria. This study provides new insights into GI evolution by performing the excision process of the inserting GI and improves our understanding of the maintenance mechanisms of composite GI.